The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.cgd.2c00188
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Integration and Defect Structure of Layered SnSe Films on PbSe/III–V Substrates

Abstract: We synthesize epitaxial films of SnSe, a van der Waals (vdW) layered semiconductor, on III−V substrates via molecular beam epitaxy. While direct deposition of SnSe on GaAs(001) surfaces results in polycrystalline growth, the structural similarity between the distorted rocksalt SnSe and a rocksalt PbSe interlayer facilitates ordered quasi-vdW epitaxy of SnSe with only discrete in-plane rotations arising from the lower film symmetry. Toward manipulating the layering of SnSe for improved mechanical, optoelectroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This is a promising development that requires confirmation and validation. Moreover, the epitaxial growth of π-SnSe on PbSe was recently reported. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a promising development that requires confirmation and validation. Moreover, the epitaxial growth of π-SnSe on PbSe was recently reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the epitaxial growth of π-SnSe on PbSe was recently reported. 36,37 Epitaxial growth is commonly expected when the lattice mismatch f between the overgrown film and the substrate (eq 1) is equal or smaller than 15%. (1) Epitaxial growth in the GaAs/PbS substrate/film system is expected considering the f = −5% (compressive) lattice mismatch.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thermoelectric (TE) materials are regarded as the most promising new clean energy sources, which can effectively ameliorate the greenhouse effect and the earth’s environment. The conversion between heat energy and electric energy can be realized directly through thermoelectric materials , that do not release any hazardous gaseous chemical residues. , The thermoelectric component is a mechanically reliable, stable environment of the electric device, with no operating mechanical vibration and noise. , To apply thermoelectric materials in the future, the key problem is improving the conversion efficiency. The thermoelectric properties are determined by a dimensionless figure of merit ( ZT ), which is defined as ZT = S 2 σ T /κ t , where S is the Seebeck coefficient, σ is the electrical conductivity, S 2 σ is the power factor (PF), T is the absolute temperature, and κ t is the total thermal conductivity, which consists of the lattice thermal conductivity (κ l ) and the electron thermal conductivity (κ e ) …”
Section: Introductionmentioning
confidence: 99%
“…1−4 The conversion between heat energy and electric energy can be realized directly through thermoelectric materials 5,6 that do not release any hazardous gaseous chemical residues. 7,8 The thermoelectric component is a mechanically reliable, stable environment of the electric device, with no operating mechanical vibration and noise. 9,10 To apply thermoelectric materials in the future, the key problem is improving the conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To realize and eventually to manufacture future nanodevices that take advantage of the large in-plane anisotropy of α-SnSe, it is important to control 90° ferroelastic domains (i.e., twins) during thin-film synthesis. To date, all reports of epitaxial thin-film synthesis of α-SnSe showed large density 90° domain boundaries (similar challenges are faced with transition-metal dichalcogenides, which grow as epitaxial thin films with a large density of 60° twin boundaries). , Since α-SnSe is a van der Waals (vdW) material, substrate–film interactions are often assumed to be weak, compared to conventional heteroepitaxial growth featuring covalent interface bonding . Even so, it has been shown that substrate–film symmetry and lattice matching can reduce the density of twin boundaries in thin films of materials grown by vdW epitaxy .…”
mentioning
confidence: 99%